Physiological Metaphor as Means of Creating the Image of Modern Russia in German Media - V. A. Babkina (Научный диалог)
The role of physiological metaphor in creating the image of modern Russia in the German media is discussed. The author relies on the idea that metaphor is one of the ways of structuring the reality and formation of the relationship of the recipient to the subject of discussion, it affects Germans’ perception of Russia, as it promotes the formation of certain ideas about the country. It is proved that among the metaphorical models in the German media, the model “Russia as a living organism” plays special role. The author believes that the physiological metaphor is the most frequently used conceptual model in connection with the feature of human consciousness to simulate the reality in his own image. Material is extracted from periodicals of Germany of 2014-2015. The text fragments that contain metaphors are analysed. The author comes to the conclusion that against the background of worsening relations between Russia and the West the physiological metaphors contribute to creating a negative image of the country, presenting the country as an aggressive actor of the international relations, who hides his own fears and insecurities behind threats. Special attention is paid to the figurative embodiment of Russia’s ability as a living organism to survive under pressure from the West.